EFFECT OF NUTRITIONAL BOLUS WITH PLANNED TEACHING PROGRAMME ON PROTEIN ENERGY MALNUTRITION - Dr. M.A. SAHBANATHUL MISSIRIYA, (International Journal of Pharma and Bio Sciences, 2014)
Childhood constitutes the foundation of adult productivity, and nutrition is the major determinant of this foundation. True experimental design was adopted to determine the effect of nutritional bolus on protein energy malnutrition among preschool children. From north Chennai, in control group 168 children and in intervention group 174 children with grade I & II malnutrition according to IAPA classification were selected randomly. Nutritional bolus is food with mixed powder(100gms) made by grinded Rice(30gms), Soya(20gms), Groundnut(20gms), Bengal gram(10gms) and Jaggery(20gms)] were provided to all children regularly for 6 months in experimental group with planned teaching pogramme on PEM. 59.8% improvement was observed after intervention. There was highly significant association between age group and sex of the children with grading of underweight, stunted and wasted and also mid-arm circumference impairment (P<0.001). The study concluded that nutritional bolus on PEM was effective to improve the nutritional status of children.